Classification of colon adenocarcinoma based on immunological characterizations: Implications for prognosis and immunotherapy - Xu, Midie; Chang, Jinjia; Wang, Wenfeng; Wang, Xin; Wang, Xu; Weng, Weiwei; Tan, Cong; Zhang, Meng; Ni, Shujuan; Wang, Lei; Huang, Zhaohui; Deng, Zhenzhong; et al. (Frontiers in Immunology, 2022)
Accurate immune molecular typing is pivotal for screening out patients with colon adenocarcinoma (COAD) who may benefit from immunotherapy and whose tumor microenvironment (TME) were needed for reprogramming to beneficial immune-mediated responses. However, little is known about the immune characteristic of COAD. Here, by calculating the enrichment score of immune characteristics in three online COAD datasets (TCGA-COAD, GSE39582 and GSE17538), we identified 17 prognostic-related immune characteristics that overlapped in at least two datasets. We determined that COADs could be stratified into three immune subtypes (IS1-IS3), based on consensus clustering of these 17 immune characteristics. Each of the three ISs were associated with distinct clinicopathological characteristics, genetic aberrations, tumor-infiltrating immune cell composition, immunophenotyping (immune “hot” and immune “cold”), and cytokine profiles, as well as different clinical outcomes and immunotherapy/therapeutic response. Patients with the IS1 tumor had high immune infiltration but immunosuppressive phenotype, IS3 tumor is an immune “hot” phenotype, whereas those with the IS2 tumor had immune “cold” phenotype. We further verified the distinct immune phenotype of IS1 and IS3 by an in-house COAD cohort. We propose that the immune subtyping can be utilized to identify COAD patients who will be affected by the tumor immune microenvironment. Furthermore, the ISs may provide a guide for personalized cancer immunotherapy and for tumor prognosis.